2021
DOI: 10.3390/ijms22179161
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cells Invade the Collateral Circulation during Human Stroke: Prospective Replication and Extension

Abstract: It remains unclear if principal components of the local cerebral stroke immune response can be reliably and reproducibly observed in patients with acute large-vessel-occlusion (LVO) stroke. We prospectively studied a large independent cohort of n = 318 consecutive LVO stroke patients undergoing mechanical thrombectomy during which cerebral blood samples from within the occluded anterior circulation and systemic control samples from the ipsilateral cervical internal carotid artery were obtained. An extensive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“… 5 While leukocyte isolation and cryopreservation led to a significant cellular loss within the granulocyte population in the study by Shaw et al., we could show by automatic cell counting that the absolute numbers of granulocytes increased within the secluded ischemic vasculature and made up the predominant leukocyte population, confirming our previous results from two independent prospective cohorts, which were based on manual cell counting. 2 , 4 In line with the data of Shaw and colleagues, we detected a shift within the lymphocyte population towards higher percentages of T cells in the ischemic compartment compared to systemic blood samples. This was due to a decrease in the number of B and NK cells, but an increase of CD4 + helper/inducer T cells at the cost of decreasing cytotoxic/suppressor CD8 + T cells.…”
supporting
confidence: 90%
See 2 more Smart Citations
“… 5 While leukocyte isolation and cryopreservation led to a significant cellular loss within the granulocyte population in the study by Shaw et al., we could show by automatic cell counting that the absolute numbers of granulocytes increased within the secluded ischemic vasculature and made up the predominant leukocyte population, confirming our previous results from two independent prospective cohorts, which were based on manual cell counting. 2 , 4 In line with the data of Shaw and colleagues, we detected a shift within the lymphocyte population towards higher percentages of T cells in the ischemic compartment compared to systemic blood samples. This was due to a decrease in the number of B and NK cells, but an increase of CD4 + helper/inducer T cells at the cost of decreasing cytotoxic/suppressor CD8 + T cells.…”
supporting
confidence: 90%
“…Local microcatheter aspiration within the cerebral ischemic arterial compartment and the cervical internal carotid artery (systemic control) was performed as previously described. 2 , 4 A cohort of patients meeting all a priori defined inclusion criteria comprised 43 patients. 2 Due to the time-critical flow-cytometry work-up, only 36 patients admitted during regular working hours could be analyzed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 12 This observation could be prospectively replicated in a large independent cohort using the exact same sampling protocol. 12 , 20 Flow cytometric automated detection and counting of leukocyte (sub-)populations again corroborated a strong predominance of neutrophils, and, in addition, disclosed a local shift in the relative distribution of lymphocytes towards CD4+ T-cells. 21 , 22 However, absolute lymphocyte numbers did not differ between local ischemic target and systemic control samples.…”
Section: The Local Neuroinflammatory Response In Human Hyper-acute St...mentioning
confidence: 86%
“…Importantly, collateral circulation may play a key role in the broad immunological response to stroke. In stroke patients, it was found that even though the extent of collateral circulation did not impact the concentration of leukocytes circulating in the blood after LVO (Tarkanyi et al, 2020), the extent of collateral circulation was an indicator of how well immune cells were able to infiltrate into the ischemic tissue of the brain (Strinitz et al, 2021). The extent of LMAs coincident with immune status, also predicts hemorrhagic complications, with patients admitted with leukopenia showing poor collateral status coupled are more at risk for intracerebral hemorrhage (Semerano et al, 2019).…”
Section: Dual Role Of Immune Modulation and Lmamentioning
confidence: 99%